Design of Enterprise Architecture Management Information System for Mosque Management (Case Study of Al Lathiif Mosque) - Cahyadi, Yadi (INFOKUM, 2022)
The mosque is the center of activity for Muslims, not only used as a place for people to gather for congregational prayers, or for major religious activities, but the mosque has a role as a place for community activities such as coaching activities, as a means of developing Islamic insights, a center for social, educational, economic activities. , and community empowerment and other positive activities that can benefit the surrounding community. The mosque has a strategic role for the progress of civilization of the people. The mosque must have facilities that support these activities. To support standard mosque management and function properly, in this case the Ministry of Religion of the Republic of Indonesia has standardized mosque management. The solution to this problem is to provide and build a system design that can provide convenience in the management of mosques according to the aspects of iarah, imarah and ri'ayah. There are several methods that can be used to simplify the manufacture of this architecture. In the case study of the Al Lathiif Mosque the researcher chose to use the TOGAF (The Open Group Architecture) method in designing enterprise architecture. The selection of the TOGAF method has four steps, namely determining the vision of the information system architecture, modeling the business architecture, and modeling the information system architecture. and technology architecture modeling. This division aims to reduce the complexity and scope of enterprise architecture development by allowing parts of the framework to be used separately or built in stages in separate projects. in the field of information technology at Masjid Al Lathiif